Revised level structure of 127Xe. (19th April 2018) - Chakraborty, S.; Sharma, H. P.; Tiwary, S. S.; Majumder, C.; Banerjee, P.; Ganguly, S.; Rai, S.; Pragati,; Mayank,; Kumar, S.; Bhattacharjee, S. S.; Singh, R. P.; et al.
Abstract: Excited states of 127 Xe were populated via fusion-evaporation reaction. A level at 2306.7 keV has been established instead of the previously reported two different levels at 2307 keV. has been assigned to this level on the basis of the DCO ratio and linear polarization asymmetry of decaying γ -rays. A weak γ -ray of 840.2 keV, decaying from this state to the state, has also been identified. Results are compared with neighboring Xe isotopes.